ANALISIS PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA PURWOREJO - , (Politeknik Sawunggalih Aji, 2021)
Tax is the largest source of revenue in the state budget. From year to year the tax revenue to the state budget menigkat always be the largest and disbanding of other sectors. The number of taxpayers from year to year is also increasing. However, increasing the amount not offset by increased taxpayer compliance in the Notice of Annual report. Tersubut compliance issues become an obstacle in maximizing tax revenue. This study examines the level of compliance of individual taxpayers registered in KPP Pratama Purworejo using independent variable understanding of tax laws and tax penalties. The purpose of this study was to analyze the influence of understanding tax laws and sanctions against tax compliance individual taxpayers registered in KPP Pratama Purworejo. The population in this study is an individual taxpayer who is registered in the KPP Pratama Purworejo. Based on data from KPP Pratama Purworejo, until 2013 the number of individual taxpayers as many as 60 300 taxpayers. Not all taxpayers have become the object of this research because their numbers are very large and for time and cost efficiency. Therefore, sampling is done with a simple random sampling method. The number of samples is determined as many as 100 individual taxpayer on KPP Pratama Purworejo. Primary data collection method is using a questionnaire (questionnaire). The data analysis technique used in this study is multiple regression analysis techniques. According to analysis carried out it could be concluded that the variable understanding of tax laws and significant positive effect on the individual taxpayer compliance with the coefficient of 0.528, while the variable tax penalties do not affect compliance tehadap individual taxpayer with a coefficient of 0.000. Variable understanding of tax laws and tax penalties together positive and significant impact on the compliance of individual taxpayers with F count 79.604. Keywords: Compliance taxpayer, understanding tax laws and tax penalties.